2019
DOI: 10.1016/j.marpetgeo.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing potential impacts of shale gas development on shallow aquifers through upward fluid migration: A multi-disciplinary approach applied to the Utica Shale in eastern Canada

Abstract: Potential impacts of shale gas development on shallow aquifers has raised concerns, especially regarding groundwater contamination. The intermediate zone separating shallow aquifers from shale gas reservoirs plays a critical role in aquifer vulnerability to fluid upflow, but the assessment of such vulnerability is challenging due to the general paucity of data in this intermediate zone. The ultimate goal of the project reported here was to develop a holistic multi-geoscience methodology to assess potential imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Surficial sediments in this region are usually thin (<10 m) and made up of reworked tills and near-shore sediments of the former Champlain Sea, except in a few areas where finegrained marine sediments have accumulated in local lows of the paleo-topography (Rivard et al 2018). Most residential wells in this region are completed into bedrock, with depths ranging from 30 to 80 m. Similarly, the monitoring wells that were drilled for the previous Saint-Édouard project (Bordeleau et al 2018a, b;Rivard et al 2019;Bordeleau et al 2019) were open-hole bedrock wells with depths between 30 and 149 m. These wells were only cased across unconsolidated units and to 2 m within the bedrock. Borehole geophysical logging revealed that the upper 60 m of bedrock, and especially the upper 30 m, contain substantial fractures (Crow and Ladevèze 2015), and is believed to be the active zone of groundwater flow (Ladevèze et al 2018).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Surficial sediments in this region are usually thin (<10 m) and made up of reworked tills and near-shore sediments of the former Champlain Sea, except in a few areas where finegrained marine sediments have accumulated in local lows of the paleo-topography (Rivard et al 2018). Most residential wells in this region are completed into bedrock, with depths ranging from 30 to 80 m. Similarly, the monitoring wells that were drilled for the previous Saint-Édouard project (Bordeleau et al 2018a, b;Rivard et al 2019;Bordeleau et al 2019) were open-hole bedrock wells with depths between 30 and 149 m. These wells were only cased across unconsolidated units and to 2 m within the bedrock. Borehole geophysical logging revealed that the upper 60 m of bedrock, and especially the upper 30 m, contain substantial fractures (Crow and Ladevèze 2015), and is believed to be the active zone of groundwater flow (Ladevèze et al 2018).…”
Section: Study Areamentioning
confidence: 99%
“…Groundwater from wells from this region is typically of good quality and is generally of the Na-HCO 3 or Na-Cl type, although some shallower wells also had Ca-HCO 3 water (Bordeleau et al 2018b). Further details of the geology and hydrogeology of the study area are presented by Lavoie et al (2014) and Rivard et al (2018Rivard et al ( , 2019.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of thermogenic methane in groundwater in the vicinity of oil and gas operations is most commonly associated with leakage from hydrocarbon wells (Jackson et al 2013;Darrah et al 2015;Rivard et al 2019). Multiple studies have shown that leaked methane from the deep subsurface migrates upward by the buoyancy resulting from density contrasts between gas and brine (Rice et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…
Studies evaluating hydrocarbon gas occurrence in shallow groundwater often include assessment of the isotopic composition of carbon (δ 13 C) and hydrogen (δ 2 H) in dissolved methane, which has been used to postulate the origin of the gas (Rivard et al, 2019;Rodrigues et al, 2019). Generally, gases formed through microbial action tend to be isotopically lighter than thermogenic gases, although there is considerable overlap in δ 13 C values between the two sources (Milkov & Etiope, 2018).
…”
mentioning
confidence: 99%